Treatment of cystoid macular edema with bevacizumab in course of Irvine-Gass syndrome - Izdebski, Bartosz; Michalewska, Zofia; Dzięgielewski, Krzysztof; Nawrocki, Jerzy; Odrobina, Dominik (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Purpose: To determine clinical effect of intravitreal bevacizumab (Avastin) in patients with cystoid macular edema after cataract surgery. Material and methods: Four eyes of four patients treated with 1 intravitreal injection of 1.25 mg Avastin. In three cases duration of cystoid macular edema was less then 4 months, in one eye cystoid macular edema was chronic (more than 4 months). Visual acuity and clinical effect in spectral optical coherence tomography (central retinal thickness and fovea anatomy) was examined before and after intravitreal injection. Results: Visual acuity improved in 3 of 4 patients. In acute cystoid macular edema final visual acuity was 0.8–0.9, in chronic cystoid macular edema patient visual acuity improved from 0.05 to 0.2. In 3 of 4 patients central retinal thickness decreased and fovea anatomy was normalized. In patient with no clinical and anatomical improvement spectral optical coherence tomography examination revealed epiretinal membrane. Conclusions: Intravitreal Avastin may be successful treatment in most Irvine-Gass syndrome cases. The condition that exclude patients from bevacizumab treatment is horizontal (epiretinal membrane), and vertical traction revealed in spectral optical coherence tomography.